A New Perspective for Implementing One Lung Ventilation Using Endobronchial Intubation in a Child - Garima Agrawal; A S, Vignesh; Raksha Kundal; Shubhangi Sudan (Journal of the Portuguese Society of Anesthesiology, 2025)
Hydatidosis caused by Echinococcus granulosus most commonly affects the lung, followed by the liver. Surgical treatment, consisting of excision of the cyst, requires anesthesia with one lung ventilation and an accompanying cysto-bronchial fistula poses an additional challenge of preventing contamination of the preserved lung during surgical manipulation. There are limited options for isolating a lung in children, especially those below 8 years of age, due to the unavailability of double-lumen tubes for this age group. One lung ventilation with an endobronchial cuffed tube, along with a coaxial suction catheter placed in the trachea, helps in preventing cross-contamination of the preserved lung. This case report demonstrates how this technique can be applied successfully in an 8-year-old child with a communicating hydatid cyst posted for emergency thoracotomy.